The Antecedents of Work-School Conflict and Work-School Enrichment - Robertson, Katelyn (Organisational Psychology, 2021)
The cost of higher education is rapidly increasing on both a global scale (Creed, French & Hood, 2015), and in the local South African context (Calitz & Fourie, 2016). This rise in costs has seen a commensurate increase in the number of university students who work, largely as a means to fund the increasing cost of their higher education (Butler, 2007; Cinamon, 2016; Owen, Kavanagh & Dollard, 2018). These working students are frequently referred to as non-traditional students in the academic literature. The psychological experiences of non-traditional students who work is a pertinent and expanding area of interest for multiple stakeholders (Owen et al., 2018). These experiences can be classified through the constructs of Work-School Conflict (WSC) and Work-School Enrichment (WSE), which refer, respectively, to the negative and positive aspects of the work-school interface (Butler, 2007). The antecedents of WSC and WSE experiences amongst nontraditional working students have to date not received any empirical attention in the South African research literature. This study aims to address this gap by contributing to the national body of knowledge in this area. The measures used were secondary self-report survey data completed by post-graduate university students who are simultaneously engaged in paid work (N=330). Multiple regression analyses indicated that time demands, job demands and social support from work explained a significant proportion of WSC; whilst job-school congruence and social support within the work context were statistically significant predictors of WSE. Moderation analyses revealed that social support at work influenced the relationship between job demands and WSC, whilst employee role saliency significantly interacted with job-school congruence to influence WSE. The results of this study are aligned to international work-school research findings, which support the additive model of job characteristics as antecedents to WSC and WSE. These results also provide deeper insight into the less explored moderation effects of work resources and demands interacting to influence WSC and WSE. Theoretical, management and educational implications of these findings are considered in relation to the existing literature.